2008
DOI: 10.1111/j.1365-2613.2008.00576.x
|View full text |Cite
|
Sign up to set email alerts
|

Single dose intravenous thioacetamide administration as a model of acute liver damage in rats

Abstract: 1Contributed equally to this study. SummaryThioacetamide (TAA) has been used extensively in the development of animal models of acute liver injury. Frequently, TAA is administered intraperitoneally to induce liver damage under anaesthesia. However, it is rarely administered by intravenous injection in conscious rats. The experiments in this study were designed to induce acute liver damage by single intravenous injection of TAA (0, 70 and 280 mg ⁄ kg) in unrestrained rats. Biochemical parameters and cytokines m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 26 publications
6
44
0
Order By: Relevance
“…The induction of the mediators in cells of portal area (mainly LMFs and biliary cells) may happen through molecules such as ROS, which have been shown to be produced in the TAA model. 34 Together with the data presented here, we suggest that upregulation of gene expression of several chemokines (mainly in LMFs and biliary cells) may be necessary to induce recruitment of inflammatory cells in a localized area beginning around the vessel walls within the portal area.…”
Section: Discussionsupporting
confidence: 82%
“…The induction of the mediators in cells of portal area (mainly LMFs and biliary cells) may happen through molecules such as ROS, which have been shown to be produced in the TAA model. 34 Together with the data presented here, we suggest that upregulation of gene expression of several chemokines (mainly in LMFs and biliary cells) may be necessary to induce recruitment of inflammatory cells in a localized area beginning around the vessel walls within the portal area.…”
Section: Discussionsupporting
confidence: 82%
“…OS participates as a critical factor in the mechanism of HE production, especially in hyperammonemic conditions (Kosenko et al, 1997;Norenberg, 2003). Results from the present study revealed marked increase in serum ammonia levels of TAA-treated rats after 6 weeks, compared to normal control that was consistent with other investigations (Chen et al, 2008;Farjam et al, 2012;Huang et al, 2012). Ammonia also reduced intracellular levels of glutathione (GSH) (Murthy et al, 2001).…”
Section: Resultssupporting
confidence: 92%
“…This leads to oxidative stress (Lena and Subramanian, 2004;Norenberg et al, 2004b), which eventually results in increased levels of lipid peroxidation products (MDA) and decreased levels of antioxidants (GSH and SOD) in TAA-treated rats. Consequently, CLF following TAA administration is well established by the elevated activities of liver transaminases (ALT and AST) in the present study, indicating cellular leakage and loss of functional integrity of hepatic membrane (Chen et al, 2008;AlAttar, 2012;Anbarasu et al, 2012;Farjam et al, 2012). The extensive liver injury induced by TAA through its free radical generation mechanism, which in turn has the ability to cause hepatic damage resulting in increased leakage of cellular enzymes.…”
Section: Resultssupporting
confidence: 50%
“…The hepatotoxic ability of TAA is well described in the literature and this drug has been extensively used in rat models of ALF and HE in sequential repeated dose administration [9,[13][14][15][16] . Once in circulation, TAA is absorbed and bioactivated by hepatocytes.…”
Section: Discussionmentioning
confidence: 99%